LITERATURE ANALYSIS: FACTORS INFLUENCING THE QUALITY OF GOVERNMENT FINANCIAL REPORTS AND GOVERNMENT ACCOUNTING ECOSYSTEM IN INDONESIA - Rani Mauliyana; Widiya Selvina; Desi Susanti; Addina Fasya; Muammar Khaddafi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Transparency and accountability in public financial management are the main pillars in realizing good governance. This study aims to systematically examine the factors that influence the quality of government financial reports in Indonesia and examine the role of the government accounting ecosystem in supporting quality financial reporting. Through a literature study of various previous studies, it was found that internal factors such as human resource (HR) competence, the effectiveness of the Government Internal Control System (SPIP), and the use of information technology play a significant role in improving the quality of financial reports. Meanwhile, external factors such as regulatory pressure, external audits, and public participation also contribute to improving the quality of reporting. However, challenges are still faced in terms of disparities in capacity between regions, cultural resistance to change, and coordination between institutions. Therefore, the development of a harmonious and sustainable government accounting ecosystem is key to realizing transparent, accountable, and quality financial reports.